IMPACT OF THE IMPAIRED IRON HOMEOSTASIS ON THE PATHOGENESIS OF ANEMIA IN PRIMARY MYELOFIBROSIS - Liana Gercheva; Stela Dimitrova; Ilina Micheva (Peytchinski Publishing, 2016)
Anemia is a well established prognostic factor in primary myelofibrosis (PMF). Recent data suggests that markers of abnormal iron homeostasis, which are known to be affected by both iron overload and inflammation, may be involved in the pathogenesis of anemia in PMF. Aim: To evaluate the relation between anemia, bone marrow fibrosis, prognostic score, survival and parameters of iron metabolism. Materials and methods: We studied 72 patients with PMF. The following parameters were analyzed: degree of bone marrow fibrosis, hemoglobin level, MCV, components of iron homeostasis (total iron binding capacity (TIBC), ferritin, serum iron). The prognostic score was determined according to IPSS and DIPSS. Statistical analysis was performed by SPSS version 19. Results: We found significant correlation between the level of hemoglobin and degree of bone marrow fibrosis and prognostic score. The MCV was analyzed in 56 of the patients and was found low in 9,5 % of them. However, there was no significant correlation between degree of fibrosis and the lower MCV. We found significant straight correlation between degree of fibrosis, serum ferritin level (p=0.006) and TIBC (p=0.018). In univariate analysis, significant feedback correlation was established between hemoglobin and serum ferritin level. Conclusion: Our results reveal the possible role of the impaired iron metabolism in the pathogenesis of anemia in PMF. Further studies are needed in order to elucidate the precise mechanisms of this process.